PENGARUH PROFITABILITY, LEVERAGE, FIXED ASSET INTENSITY, INVENTORY INTENSITY, DAN FIRM SIZE TERHADAP MANAJEMEN PAJAK (Studi Empiris pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2021–2024) - Pandu Imam Nugroho; Dul Muid (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Profitability, Leverage, Fixed Asset Intensity, Inventory Intensity, and Firm Size on tax management in energy sector companies listed on the Indonesia Stock Exchange for the period 2021–2024. Tax management in this study is proxied using the Effective Tax Rate (ETR). This study is motivated by the phenomenon of tax management practices in large companies and the research gap from previous studies that show inconsistent results regarding the factors that influence tax management.This study uses a quantitative approach with secondary data in the form of annual financial reports of energy sector companies obtained through the official website of the IDX. The sampling technique used purposive sampling based on specific criteria, resulting in a sample of companies that met the requirements during the observation period. The data analysis method used was multiple linear regression analysis with the help of SPSS version 25, which had previously undergone classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity tests.The results of the study indicate that Leverage and Fixed Asset Intensity have a positive effect on tax management. Conversely, Profitability, Inventory Intensity, and Firm Size have a negative effect on tax management in energy sector companies. These findings can be taken into consideration by company management.